Comparison of System Concepts for Traffic Monitoring with Multi-Channel SAR - Gabele, Martina; Baumgartner, Stefan V.; Krieger, Gerhard; Bethke, Karl-Heinz (European Conference on Synthetic Aperture Radar (EUSAR), 2006)
This paper addresses the ground moving target indication (GMTI) performance of space-based multi-channel synthetic aperture radar (MSAR) systems as they suffer from the high speed of the radar platform leading to a wide spread clutter spectrum and compares it with the air-based case. Opposite to classical GMTI systems near future space-based SAR systems offer only few simultaneous channels and relatively low pulse repetition fre-quency (PRF). The influences of PRF, antenna size and number of channels on detection performance are stud-ied. The analysis is based on a post-Doppler approach of the optimal processor since this has the advantage that in case of stationary clutter the clutter contributions can be assumed statistically independent for each Doppler cell.
DLR Import::2019-04-03